Dietary vitamin C and folic acid supplementation ameliorates the detrimental effects of heat stress in Japanese quail - Şahin, Kazım; Onderci, M; Şahin, Nurhan; Gursu, MF; Küçük, Ömer (Elsevier Science Inc, 2003)
We evaluated the effects of vitamin C (L-ascorbic acid) and folic acid supplementation on performance, carcass characteristics and concentrations of the oxidative stress markers [malondialdehyde (MDA), homocysteine], adrenocorticotropic hormone (ACTH), vitamins C, E, A, B-12 and folic acid, and mineral status in broiler Japanese quail (Coturnix coturnix japonica) exposed to high ambient temperature (34degreesC, 8 h/d, 0900-1700 h). The birds (n = 150; 10-d-old) kept at 34degreesC were fed a basal diet (HS group) or the basal diet supplemented with 250 mg of L-ascorbic acid/kg of diet (Vit C group), 1 mg of folic acid/kg of diet (FA group) or both (Vit C + FA group), whereas birds kept at 22degreesC were fed the basal diet (TN group). Supplementing heat-stressed quail with vitamin C and folic acid improved performance compared to the HS group. Effects generally were greatest in quail supplemented with both. Although supplementation did not consistently restore concentrations to those of the TN group, it increased serum concentrations of the vitamins under study. Furthermore, serum and tissue MDA, homocysteine and ACTH concentrations were lower in the supplemented groups than in the heat-stressed controls. Retention of N, ash, Ca, P, Zn, Fe, Cu and Cr were highest in the Vit C + FA group and lowest in the HS group (P < 0.05). The results of the study indicate that vitamin C and folic acid supplementation attenuates the decline in performance and antioxidant status caused by heat stress. Such supplementation may offer protection against heat stress-related depression in performance of Japanese quail. J. Nutr. 133: 1882-1886, 2003.
Keywords: folic acid; heat stress; homocysteine; quail; vitamin C